Drug-induced severe sideroblastic anemia following combined olanzapine and fluvoxamine therapy: a case report - Zhang, Xinru; Zhang, Anan; Zhang, Jinmei; Hu, Dandan (Frontiers in Psychiatry, 2025)
Olanzapine and fluvoxamine are commonly used psychotropic medications for treating anxiety and depressive disorders, particularly in cases with psychotic symptoms or treatment-resistant presentations. Although there are occasional reports of hematologic toxicity with monotherapy of these two drugs, no clear reports in the existing literature have documented severe sideroblastic anemia induced by their combination. Notably, as a potent CYP1A2 inhibitor, fluvoxamine significantly inhibits the metabolism of olanzapine, leading to elevated plasma concentrations. This pharmacokinetic synergy may exacerbate the risk of myelosuppression, although the specific mechanism remains to be elucidated. This article presents the first documented case of a 78-year-old male patient with chronic obstructive pulmonary disease (COPD) who developed severe anemia (nadir hemoglobin 37 g/L) after the combined use of olanzapine and fluvoxamine. Through systematic etiological investigation, bone marrow morphology findings, and the Naranjo Adverse Drug Reaction Probability Scale (score 9, indicating a clear association), the diagnosis was confirmed as drug-induced severe acquired sideroblastic anemia. This case underscores the importance of thoroughly evaluating blood system safety when combining psychotropic medications in elderly patients with chronic diseases, and highlights the need for enhanced dynamic monitoring to identify and intervene in potential adverse reactions at an early stage.